1996
DOI: 10.1017/s0022112096001619
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced dispersion in a dilute suspension of rough spheres

Abstract: In the absence of Brownian motion, inertia and inter-particle forces, two smooth spheres collide in a simple shear flow in a reversible way returning to their initial streamlines. Because the minimum separation during the collision can be less than 10−4 of the radius, quite a small surface roughness can have a significant irreversible effect on the collision. We calculate the change between the initial and final streamlines caused by roughness. Repeated random collisions in a dilute suspension lead to a diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
243
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(266 citation statements)
references
References 9 publications
19
243
2
2
Order By: Relevance
“…Such surface asperities promote an early contact and impose the surface-to-surface separation between particles and the magnitude of lubrication stress consequently. Surface roughness can therefore significantly modify the rheological properties and the microstructure of suspensions, as confirmed by many numerical studies (Sierou & Brady 2002;Drazer et al 2002Drazer et al , 2004DaCunha & Hinch 1996). Theoretical studies in dilute regimes show that large roughness can decrease viscosity as well as increase |N 1 | and |N 2 | (Wilson 2005;Wilson & Davis 2002;Davis et al 2003;Zarraga & Leighton Jr 2001).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Such surface asperities promote an early contact and impose the surface-to-surface separation between particles and the magnitude of lubrication stress consequently. Surface roughness can therefore significantly modify the rheological properties and the microstructure of suspensions, as confirmed by many numerical studies (Sierou & Brady 2002;Drazer et al 2002Drazer et al , 2004DaCunha & Hinch 1996). Theoretical studies in dilute regimes show that large roughness can decrease viscosity as well as increase |N 1 | and |N 2 | (Wilson 2005;Wilson & Davis 2002;Davis et al 2003;Zarraga & Leighton Jr 2001).…”
Section: Introductionmentioning
confidence: 75%
“…Due to the imposed shear flow, the spheres will hydrodynamically interact and possibly touch in the case of rough spheres. A theoretical reference solution is computed using the approach already presented in other works (DaCunha & Hinch 1996;Zarraga & Leighton Jr 2001;Metzger et al 2013). The relative trajectories are integrated in time using the theoretical resistance functions R 2B theo .…”
Section: A Pair Of Rough Frictional Spheres In a Shear Flowmentioning
confidence: 99%
“…Da Cunha and Hinch [36] clearly demonstrated that shear induced self-diffusion is function of the strength of repulsive forces which yield a net displacement at each pairwise particle interaction. Particles are moving across streamlines enhancing cross-stream diffusion (adhesion to wall occurs sooner).…”
Section: Channel Permeabilitymentioning
confidence: 99%
“…where the mobility functions A and B are functions only of r. Here, we shall use the expressions for these functions given by da Cunha & Hinch (1996), who divided the interval r > 2 into three different regions (see da Cunha & Hinch (1996) for details on how they obtained the expressions for A and B in each region). Specifically: a) within the lubrication region 2 < r ≤ 2.01,…”
Section: Microscopic Structure Induced By the Shearmentioning
confidence: 99%
“…For two freely-moving spheres in a simple shear flow, the velocity fluctuation of a sphere induced by a second sphere the center of which is located at r is given by (da Cunha & Hinch 1996):…”
Section: Velocity Fluctuationsmentioning
confidence: 99%